2008
DOI: 10.1080/09286580802435179
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Diabetic Retinopathy in a Multi-Racial Underserved Population

Abstract: In this population of similar socioeconomic status and access to healthcare, race was not an independent predictor of diabetic retinopathy. This suggests that racial differences described in previous studies may be eliminated when social factors are equalized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 16 publications
2
13
0
Order By: Relevance
“…5 A similar study identified longer duration of diabetes and use of oral hypoglycemic medication or insulin as significant independent predictors of DR in a multi-racial undeserved population. 8 In both studies, race was not an independent predictor for development of DR. 5,8 Identifying risk factors for DR in patients with diabetes may help to identify a subgroup of patients with higher priority for DR screening and improve early screening rates for those at highest risk. We therefore investigated a cohort of patients who were screened for DR in our telemedicine program to identify predictors of DR in a large Federally Qualified Health Center (FQHC) patient population.…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…5 A similar study identified longer duration of diabetes and use of oral hypoglycemic medication or insulin as significant independent predictors of DR in a multi-racial undeserved population. 8 In both studies, race was not an independent predictor for development of DR. 5,8 Identifying risk factors for DR in patients with diabetes may help to identify a subgroup of patients with higher priority for DR screening and improve early screening rates for those at highest risk. We therefore investigated a cohort of patients who were screened for DR in our telemedicine program to identify predictors of DR in a large Federally Qualified Health Center (FQHC) patient population.…”
mentioning
confidence: 74%
“…Race/ethnicity, age, BMI, tobacco use, sex, blood pressure or blood pressure control, being insured, and the presence of heart disease or hyperlipidemia were not independent predictors of DR in our population. Several other multi-racial studies have also found that these factors or characteristics, with the exception of heart disease or hyperlipidemia, are not significantly associated with DR. 5,6,8 As the incidence of DR increases with exponential growth in the number of patients with diabetes, 2,3 it will be important for clinicians who care for patients with diabetes to be aware of the risk to their patients. In addition, practices serving racial/ ethnic minorities, who have disproportionately higher prevalence and increased severity of DR 5,6 and may have limited resources, will need direction on how best to allocate these resources to screen those at highest risk.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic inflammation develops in the retinal microvasculature under sustained hyperglycemia (Abu El-Asrar et al, 1992;Meleth et al, 2005) and is implicated in the pathogenesis of diabetic retinopathy. Proliferative DR (PDR) is followed by recurrent vitreous hemorrhages, traction retinal detachment, retinal and vitreous fibrosis, and optic nerve atrophy, which finally lead to severe visual impairments (Abu El-Asrar et al, 2006;Bhavsar, 2006;Lim et al, 2008). Retinal neovascularization (RNV) is the most striking characteristic of PDR (Du et al, 2014) and involves various angiogenic factors such as cytokines, inflammatory cells, and growth factors (Adamis, 2002;Abu El-Asrar et al, 2006;Patel et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…These include the duration of diabetes mellitus, completeness of conducted comprehensive treatment, the effectiveness of the control of glucose level in blood serum and a number of other factors. The progression of diabetic retinopathy may be complicated by recurrent intraocular hemorrhage, retinal and vitreous fibrosis, traction retinal detachment, optic atrophy, which leads to the development of irreversible blindness [1,[4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Questions remain about the role of pro-inflammatory, anti-inflammatory and regulatory cytokines in diabetic retinopathy. The relationship of cytokines with the factors activating proliferation, also requires further study [4,10].…”
Section: Introductionmentioning
confidence: 99%